PENGEMBANGAN MORAL ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL PETAK UMPET - Lorenza, Dina Dwi; Prasetiya, Benny (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
Early childhood education is very important for children's growth and development from an early age because during early childhood or what is called the golden age, 90% of your child's brain development is very good and is an important foundation to support your child's learning abilities. Playing is one way to increase children's potential at an early age. This research contradicts the increasing incidence of modern game addiction which is detrimental to children, because nowadays children like to play gadgets which can harm themselves, in contrast to the potential of traditional games which contribute to moral development. The safety of traditional games for young children is a focus because these games are an inseparable part of the nation's cultural wealth which contains benefits and moral values ​​such as honesty, patience, perseverance, responsibility and mutual respect for others. This research aims to strengthen the moral development of young children through the traditional game of hide and seek. The approach applied in this research is qualitative by collecting data through direct observation and documentary recording. Keywords: Traditional Games, Hide and Seek, Morals, Early Childhood